UNIT PRICE CONTRACT IN CONSTRUCTION WORK - Herawan Sauni; Yosep Fery Yorizal Fery Yorizal (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
According to Presidential Regulation No. 54 of 2010 article 50 paragraph (3) there are 5 (five) contract of procurement goods and services based on payment namely lump sum contract, unit price contract, the combination of lump sum and unit price contract, percentage contract and turnkey contract. Of those five contract types, lump sum and unit price contracts are the most common contract applied in construction work; but other types are also possible to be applied. Government Regulation No. 29 of 2000 article 21 paragraph (2) states “Construction work contract of unit price payment as stated in article 20 paragraph (3) part a number 2 is a contract on services for each completed unit of work within the time given with fixed price for each unit based on volume of work done by service Supplier”. However, there are many service Suppliers in Department of Public Works that do not fully understand about unit price contract in construction work. Thus, the objective of this study is to find out the important considerations in applying unit price contract in work construction.